The effects and safety of PD‐1/PD‐L1 inhibitors on head and neck cancer: A systematic review and meta‐analysis. (22nd August 2019) - Wang, Bi‐Cheng; Cao, Ru‐Bo; Li, Pin‐Dong; Fu, Chen
Abstract: Background: Inhibitors of programmed cell death‐1 (PD‐1) and its ligand (PD‐L1) have been increasingly used in head and neck cancer therapy and reported to improve the outcomes with an acceptable safety profile. This systematic review and meta‐analysis was conducted to assess the benefit and risk of PD‐1/PD‐L1 inhibitors in patients with head and neck cancer. Method: The PubMed, Cochrane Library, EMBASE and Web of Science databases were systematically searched to find potentially eligible studies up to May 30, 2019. Primary outcomes were overall survival (OS), progression‐free survival (PFS), objective response rate (ORR), disease control rate (DCR) and adverse events. Results: Overall, this analysis consisted of nine eligible studies, with two randomized controlled trials and seven single arm trials. In the treatment of recurrent or metastatic head and neck cancer, PD‐1 inhibitors showed significantly lower relative risk of death than standard‐of‐care therapy (odds ratio [OR] = 0.60, 95% confidence interval [CI]: 0.44‐0.82, I 2  = 0%, P  = .001). Programmed cell death‐1 inhibitors also decreased the risk of disease progression, however, there was no statistically significant difference of PFS between the treatments (OR = 0.69, 95% CI: 0.48‐1.01, I 2  = 0%, P  = .05). Subgroup analysis showed that human papillomavirus (HPV) positive patients had higher response rates than HPV negative patients in PD‐1/PD‐L1 inhibitors‐treated population (ORR: 18.8% vs 12.2%; DCR: 42.8% vs 34.4%). The most common any‐grade and grade ≥3 treatment‐related adverse events were fatigue (14.7%, 95% CI: 12.3%‐17.1%) and aspartate aminotransferase increased (1.6%, 95% CI: 0.3%‐2.9%), respectively. Conclusion: Programmed cell death‐1 inhibitors prolonged OS in comparison with standard‐of‐care therapy in recurrent or metastatic head and neck cancer patients. Human papillomavirus positive patients were superior to HPV negative patients in the treatment of PD‐1/PD‐L1 inhibitors. More phase III randomized controlled trials are warranted to confirm our findings. Abstract : Forest plots of overall survival and progression‐free survival for the meta‐analysis. A, Forest plot of odds ratio for overall survival in head and neck patients between PD‐1/PD‐L1 inhibitors and standard‐of‐care therapy. B, Forest plot of odds ratio for progression‐free survival in head and neck patients between PD‐1/PD‐L1 inhibitors and standard‐of‐care therapy. CI, confidence interval; Fix, fixed effect analysis model; I 2, index of heterogeneity; M‐H, Mantel‐Haenszel statistical method.